Hell yeah. Volume one, Last day on Earth - Keatinge, Joe (Image ; Diamond [distributor]], 2012)
"Today is the worst day of Benjamin Day's life. He's the poster child for the first generation raised in a world where superheroes exist, but he wants nothing to do with super-anything. When versions of himself from throughout the multiverse show up dead, this one-man crisis of infinite selves tears open twenty-year-old secrets. Ben's now forced into the super-society he's long denied"--Back cover.